2020
DOI: 10.3390/nu12020406
|View full text |Cite
|
Sign up to set email alerts
|

Acute Caffeine Intake Enhances Mean Power Output and Bar Velocity during the Bench Press Throw in Athletes Habituated to Caffeine

Abstract: Background: The main objective of the current investigation was to evaluate the effects of caffeine on power output and bar velocity during an explosive bench press throw in athletes habituated to caffeine. Methods: Twelve resistance trained individuals habituated to caffeine ingestion participated in a randomized double-blind experimental design. Each participant performed three identical experimental sessions 60 min after the intake of a placebo, 3, and 6 mg/kg/b.m. of caffeine. In each experimental session,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 60 publications
7
56
0
Order By: Relevance
“…Therefore, the use of a deceptive protocol to induce the placebo effect of caffeine is likely an ineffective measure to enhance muscle performance in women athletes who are habituated to caffeine. To this respect, the actual ingestion of caffeine may be recommended [7] although doses higher than the daily level of its consumption may be necessary to obtain the potential ergogenic effect of caffeine in athletes habituated to this substance [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the use of a deceptive protocol to induce the placebo effect of caffeine is likely an ineffective measure to enhance muscle performance in women athletes who are habituated to caffeine. To this respect, the actual ingestion of caffeine may be recommended [7] although doses higher than the daily level of its consumption may be necessary to obtain the potential ergogenic effect of caffeine in athletes habituated to this substance [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, urinary caffeine concentration has increased since the removal of caffeine from the list of banned substances of the World Antidoping Agency in 2004 suggesting an increasing use of this stimulant in elite sport [2]. In the last years, there has been a burst of research that supports the performance-enhancing effects of caffeine across a wide range of sporting activities including aerobic exercise [3] anaerobic-like exercise [4], and resistance exercise [5][6][7]. Overall, there is ample consensus to consider the antagonistic role of caffeine and its two metabolites, paraxanthine and theophylline, in adenosine receptors as the main mechanism behind its ergogenic effects during exercise, as caffeine can bind adenosine A 1 , A 2A and A 2B receptors in the central nervous system, reducing the fatiguing effect of adenosine [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering et al [38] suggested that the reduction in the ergogenic effects of CAF in habitual users can be modi ed using doses greater than the daily habitual intake, however a study by Wilk et al [1,2] showed no bene ts (except in maximal strength) from acute ingestion of CAF when the doses of CAF were above their habitual intake. In another study, Wilk et al [39] found a positive effect of CAF (3 and 6 mg/kg/b.m.) on mean power output and mean bar velocity during the bench press throw in athletes habituated to CAF, and performance enhancements were obtained even when the dose of CAF did not exceed the value of habitual consumption.…”
Section: Introductionmentioning
confidence: 89%
“…The threshold used to classify individuals as high caffeine consumers varied from 190 mg/day [19] to more than 600 mg/day [20]. In addition, only three studies estimated daily caffeine intake in relation to body mass [21][22][23]. In those investigations that used absolute values to assess the level of habituation to caffeine, the findings could lead to incorrect conclusions because the same absolute amount of caffeine (in mg/day) would have a different impact on subjects with different body mass.…”
Section: Abstract: Classification; Habituation; Caffeine Users; Dailymentioning
confidence: 99%